Electrical withstand performance of Malaysian based palm oil under influence of HVDC stress - Haliap, Mohd Kharul Anuar; Baharom, Md Nor Ramdon; Muhammad Saufi, Zainab Zainal; Ishak, Mohd Taufiq; Ullah, Irshad; Othman, Nordiana Azlin (Penerbit UTHM, 2020)
Overvoltage is a phenomenon where electrical waveform applied to circuit or device exceeds normal operating parameters. The sources of overvoltage are often unpredictable and can lead to permanent degradation, failure or temporary malfunction of devices and systems. Equipment running with HVDC needs to be equipped with a proper protection system and insulation strength properties better than typically being rated to the HVAC system.